Oral intake of Boesenbergia pandurata extract improves skin hydration, gloss, and wrinkling: A randomized, double‐blind, and placebo‐controlled study. (18th April 2017) - Kim, Do Un; Chung, Hee Chul; Kim, Changhee; Hwang, Jae‐Kwan
Summary: Background: Photoaging is a severe skin damage that occurs as a result of exposure to external elements, primarily ultraviolet (UV) irradiation. Chronically, UV‐irradiated skin exhibits the signs of sunburn and hyperpigmentation with the destruction of connective tissues. Previously, Boesenbergia pandurata ( B. pandurata ) and its active compound panduratin A showed antiphotoaging activities in vitro and in vivo. Objective: The aim of this study was to investigate the clinical efficacy of B. pandurata intake on skin hydration, gloss, wrinkling, and elasticity. Methods: A double‐blind, placebo‐controlled trial was conducted to clinically evaluate the effect of B. pandurata ethanol extract (BPE) containing 8% of panduratin A on human skin hydration, gloss, wrinkling, and elasticity. Ninety‐two subjects were randomly assigned to receive tablets containing either BPE or placebo for 12 weeks. Results: The test group had significantly increased skin hydration and gloss and decreased wrinkling compared to the placebo group at 12 weeks. There was no significant difference in skin elasticity between the two groups; however, the increment rate in the test group was higher than that in the placebo group at 12 weeks. None of the subjects developed adverse symptoms during the study period. Conclusion: These results suggest that BPE can be used as a nutraceutical or nutricosmetic material for improving human skin hydration, gloss, and wrinkling.